2012
DOI: 10.1111/j.1365-4632.2012.05616.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology life quality index scores in children with vitiligo: comparison with atopic dermatitis and healthy control subjects

Abstract: Vitiligo and atopic dermatitis (AD) are two major cutaneous diseases that affect quality of life (QoL) by causing functional and psychosocial disorders. Our objective was to calculate Children's Dermatology Life Quality Index (CDLQI) scores in children with vitiligo and to compare these values with those in AD patients and healthy control subjects. The CDLQI was completed for 50 vitiligo and 50 AD patients presenting at the dermatology polyclinic, as well as for 50 age- and sex-matched healthy controls. All su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Total CDLQI scores were categorized as no or small (0–5), moderate , and very or extremely large (>10) QOL effect [as previously reported ], owing to a highly skewed distribution of results. Ordinal logistic regression models were constructed to examine the effect of vitiligo extent on QOL, with categorized CDLQI and individual aspects of the CDLQI divided into four responses (not at all, only a little, quite a lot, very much) as the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Total CDLQI scores were categorized as no or small (0–5), moderate , and very or extremely large (>10) QOL effect [as previously reported ], owing to a highly skewed distribution of results. Ordinal logistic regression models were constructed to examine the effect of vitiligo extent on QOL, with categorized CDLQI and individual aspects of the CDLQI divided into four responses (not at all, only a little, quite a lot, very much) as the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Almost 90% of patients have been asked questions about their white spots by strangers (25), 66% described staring at them (18), almost 50% experienced rude remarks (25,26) and 8-13% reported discrimination at work (18,27). Importantly, the knowledge about children's life with this disease has greatly improved (28)(29)(30)(31)(32). Recently our own data showed that stigmatisation was highly significant on well-being of youngsters, often leading to an impaired QoL, avoidance of situations or concealing of the white spots (33).…”
mentioning
confidence: 96%
“…A limited number of studies exist in the literature that aims to evaluate emotional burden caused by vitiligo and the effect of the illness on psychosocial development, specifically in children and adolescents [25]. As there is one study that reported worse quality of life among children with vitiligo, compared to those with atopic dermatitis [26], Bilgic et al [27] have also reported that for prepubertal children, severity of vitiligo correlated with severity of depression, while in adolescents, lower levels of life quality have been reported especially if the lesions were located in body parts that were visible to others. In cases with lesions located in visible body regions, it has been reported that stigma related to the disorder might pose an increased risk for developing a psychiatric illness or a disorder, along with lower levels of quality of life, assessed [7,14,28].…”
Section: Introductionmentioning
confidence: 99%